Caricature and headache - Oliveira, Daniella Araújo de; Silva, Louana Cassiano da; Silva, Dayzene Freitas da; Silva, Gabriela Almeida da; Queiroz, Mariana Luiza da Silva; Oliveira Filho, Marcos Antônio de; Costa, Rafael; Valença, Marcelo Moraes (Headache Medicine, 2015)
The authors comment on the use of caricature to represent a migraine sufferer and show a caricature of a woman with migraine drawn by an artist from Goiânia, Goias State, Brazil.